SELECTED CELLULAR IMMUNITY INDICATORS IN DIAGNOSTICS OF ACUTE MESENTERIAL ISCHEMIA - Z. A. Artamonova; E. V. Namokonov (Acta Biomedica Scientifica)
Background. The problem of early diagnosis of acute mesenteric ischemia is still relevant today. In this connection, it is of interest to search for a diagnostic marker of this pathological condition. Up to 80 % of all immunocompetent cells are localized in the intestinal mucosa. So, we can assume that the mesenteric channel occlusion can result in changes in the subpopulation structure of lymphocytes. The aim of the study is to analyse some parameters of the subpopulation structure of lymphocytes at various stages of acute mesenteric ischemia in the experiment. Materials and methods. The experiment was performed on 32 adult male rats - with an average mass of 200 g. The animals were divided into 4 equal groups. The first group was a control group. All other animals underwent laparotomy, blood sampling from the posterior vena cava, ligation of the mesenteric artery at the base of the mesentery root, suturing the wound. After 3, 6 and 8 hours, blood sampling, small bowel biopsy were performed in the second, third and fourth groups. The subpopulation structure of lymphocytes was assessed by direct immunofluorescence staining. Morphological material was stained with hematoxylin-eosin. Results. The complete occlusion of the cranial mesenteric artery was revealed to be accompanied by a decrease in the lymphocytes level, an increase in CD4/CD8 ratio. Conclusion. The data obtained were to develop a diagnostic method for acute mesenteric ischemia (Patent N 2552338, Russian Federation).